Study of ectoparasite prevalence and intensity on mud crab (Scylla serrata) in mangrove area of Wonorejo, Surabaya - Purna, Selobing; Munir, Misbakhul; Maisaroh, Dian Sari (UIN Sunan Ampel Surabaya, 2021)
This study aims to know various types, prevalence, and intensity of ectoparasite on mud crab (Scylla serrata) in mangrove area Wonorejo, Surabaya. This study used survey method with random sampling to collect the data. This study was conducted in July-December 2020. Ectoparasite in this study collected by smear method. In-situ water quality measurement were applied in this study. Mud crab in this study was obtained from local fisherman that consist of 30 crabs. There are 3 types of ectoparasite was infected mud crab there are Octolasmis sp. (208 ind), Zoothamnium sp. (93 ind), and Epistylis sp. (116 ind). Those ectoparasite was found in mud crabs gills. The highest prevalence was Octolasmis sp. (70%), Epistylis sp. (30%), and Zoothamnium sp. (23%). The highest intensity was Zoothamnium sp (13.29 ind/crab), Epistylis sp. (12.89 ind/crab), and Octolasmis sp. (9.90 ind/crab). Based on Ministerial Decree of Ministry Environment and Forestry No. 1 of 2004 water quality in Wonorejo mangrove area was still optimal for life cycle of mud crab with average of temperature is 31.20°C, Dissolved Oxygen 5.53 mg/l, salinity 11 ppt, and pH 7.40.